The Picturesque : Architecture, Disgust and Other Irregularities. - Macarthur, John (The Classical Tradition in Architecture Series, 2006)
In this fresh and authoritative account John Macarthur presents the eighteenth century idea of the picturesque - when it was a risky term concerned with a refined taste for everyday things, such as the hovels of the labouring poor - in the light of its reception and effects in modern culture.